As dificuldades de pronúncia de aprendizes Hispano-Americanos do Português Brasileiro - Almeida, Ivaneide Sena de (2017)
This dissertation is situated in Brazilian Portuguese Pronunciation area and has as its theme the difficulties of pronunciation of Spanish-American learners of Brazilian Portuguese. Its general objective is to contribute to the improvement of the pronunciation of Brazilian Portuguese by Hispanic American learners. The specific objectives are: To diagnose the difficulties of pronunciation of Hispanic American learners. Find some perspectives for the improvement of these apprentices, using the language laboratory. The research carried out selected five informants for whom recordings of recorded journals were collected. The recordings were transcribed and the diagnosis of the difficulties was performed with the standardized pronunciation of the Brazilian Portuguese, as published by Globo TV in national and international territory. The diagnosis of pronunciation difficulties indicates that Spanish-American learners, when starting at the intermediate level, have difficulty in pronunciation resulting from the interlanguage phase, that is, they perform Portuguese-language sounds guided by the articulations of their native pronunciations. The diagnosed difficulties were detected from the syllabic center accentuated in contrast to the syllabic unaccented syllabus, differentiating oral vowels from the nasal ones. The articular difficulties of the consonants were detected from the initial and final syllable nodes. With the difficulty diagnosed, it is intended to show a didactic resource for the teaching of the pronunciation of Brazilian Portuguese, according to the "globes", proposed by Silveira (2008), to be used in the language laboratory of PUC / SP. Each exercise is accompanied by articulatory descriptions, followed by distinctive oppositions and non-distinctive oppositions, but which characterize combinatorial variants for syllabic sequences in words